Deteksi Pencemaran Bakteri Salmonella sp. Pada Udang Putih (Penaeus merguiensis) Segar Di Pasar Tradisional Kotamadya Surabaya [Pollution Detection Of Salmonella sp. To Fresh White Shrimp (Penaeus merguiensis) At Traditional Market Of Surabaya Residence] - Hasutji Endah Narumi; Zuhriansyah Zuhriansyah; Imam Mustofa (Faculty of Fisheries and Marine Universitas Airlangga, 2009)
Abstract The aim of this study were to know the level of contamination againts Salmonella sp. bacteria in fresh white shrimp at the traditional market in surabaya. The fresh white shirmp were collect from 5 areas in Surabaya (East, South, Center, North and West). Total samples were 25 (five samples for each area) dan each sample were weight 100 gram. Sample from each area were using mortar and making for a suspention to take the isolate. More over using SPSS medium for enriched them further more were observed under the microscope also were test for the biochemistry characteristics. Data from the enrichment for Salmonella sp. bacteria were descriptive analyze and to know the level of contaminations we used chi-square : the result of this study were indicate that the fresh white shrimp at the traditional market in Surabaya were contaminated with Salmonella sp. bacteria, but they didn't show the significant different at the contaminant fish levels (p > 0,05).